(untitled) (Journal of Nuclear Technology in Applied Science, 2024)
Chrysophyllum albidum is native to tropical Africa. This seasonal plant has been found to contain more vitamin C than most fruits. In this study, gamma irradiation which offers an option of disinfecting and elongating the shelf life of fruits will be employed to improve the shelf life of C.albidum.Pest free fruits plucked at maturity were washed with brine and cleaned with ethanol. Four sets of fruits were irradiated with different gamma doses: 0, 250, 300 and 600 Gy. Moisture, Phenol, flavonoid and ascorbic acid content were determined for the various batches at weekly intervals. DPPH radical scavenging activities, total heterotrophic count, E. coli count, coliform count and fungal count were also determined.The percentage of the fruit that got spoilt with 300 Gy are 4.5%, 21.43% and 66.67% for week one, two and three respectively. The moisture content of all the batches ranged from 51.3 to 58.2%. Fresh sample of C.albidum has similar DPPH Radical Scavenging percentage inhibition as ascorbic acid. The flavonoid, phenol and ascorbic acid concentrations were 3.716, 1.107 and 1.585 mg/g respectively. The result showed almost no growth in total heterotrophic count, E. coli count, coliform count and fungal count for most of the irradiated samples.